MP-11 Eimeria pragensis Induce Immune Mediated Intestinal Hypomotility in C57BL/6 Mice - Riki Siswadi; Ayako Yoshida; Hiroyuki Satoh; Nariaki Nonaka (Hemera Zoa, 2018)
The manifestation of intestinal dysmotility of coccidiosis has never been briefly reported before. From murine Eimeria study we concluded that Eimeria pragensis (Ep) is capable to induce intestinal hypomotility described to be similar to pan-enteric ileus.In comparison with the intestinal dysmotility in postoperative ileus which is orchestrated by TH1 immune response [1], a local injury to some part of intestine could trigger pan-enteric ileus. If the TH1 immune response could also be induced in Ep infection, the delay in intestinal motility could be explained as similar mechanism as the post-operative ileus. Since the Ep infestation occurred in the ileocecal part of the intestines, with similar mechanism of post-operative ileus, the pan-enteric ileus could be triggered. In this study, we tried to find a relationship between intestinal dysmotility and TH1 immune response in murine coccidiosis.